KATA TANYA DALAM KALIMAT TANYA BAHASA INGGRIS DAN BAHASA WAYOLI SUATU ANALISIS KONTRASTIF - Ditty, Denny Frandky (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI)
ABSTRACT This study is an attempt to describe and analyze English and Wayoli language which focuses on the question words in interrogative sentences in relation to their form and functions in the both languages. The English data have been collected from several books, whereas the data of Wayoli language have been collected by interviewing from some informants the research questions are what are the forms of question words in interrogative sentence in English and Wayoli Language? And what are the similarities and differences of both two language in terms of question words in interrogative sentence in those two language?. The data will be described and analyzed descriptively in terms of their forms and function by using Aarts and Aarts; Murphy in terms of form and Tracy in terms of function. The result shows that English and Wayoli language have the similarities and differences in terms of question word (wh-question). Those are: who, when, how, why, what, where, which (question words of English), question words of Wayoli language are: giyana, thumduo, sha’alou, I’arhou, ohrou, ale’a, ngale’a (question words of Wayoli language). The differences can be seen in those two languages. In English there are three forms of interrogative sentences, whereas inWayoli language there is only one form of interrogative sentences. The English interrogative sentences always use auxiliary verbs, whereas Wayoli language doesn’t. ---------------------------------------------------------------------------------------------------------- Keywords: Question words, English and Wayoli Language, Contrastive Analysis.